Anterior Retropharyngeal Reduction and Sequential Posterior Fusion for Atlantoaxial Rotatory Fixation With Locked C1–C2 Lateral Facet. Issue 21 (November 2015) - Qi, Chen; Xi, Yang; Chunguang, Zhou; Limin, Liu; Yueming, Song
Abstract : Study Design: Retrospective case series. Objective: To introduce a new type of atlantoaxial rotatory fixation (AARF) with a locked C1–C2 lateral facet and evaluate its therapeutic strategy. Summary of Background Data: AARF presenting with torticollis and limited neck motion is commonly seen in teenagers. Fielding and Hawkins' classification is generally applied to AARF. Although conservative treatment is effective for acute AARF, it is often unsuccessful for chronic AARF, which ultimately requires surgery. We introduce a new type of chronic AARF with a locked C1–C2 lateral facet that does not fit into Fielding and Hawkins' classification and describe the appropriate treatment. Methods: Eight patients who had chronic AARF with a unilaterally locked C1–C2 lateral facet were referred to our clinic. Reduction had failed after traction for 3 to 4 weeks. After open release and reduction using the anterior retropharyngeal approach, we applied posterior C1–C2 transpedicular screw fixation with an autologous iliac bone graft for stage I or II. Results: The anterior retropharyngeal approach provided direct access to the C1–C2 locked lateral facet. The patient in an overall poor condition (stage II) underwent delayed posterior C1–C2 arthrodesis. The others (stage I) underwent immediate posterior C1–C2 arthrodesis. All patients were followed up for an average of 14.8 months (5–37 mo). Three-dimensional computed tomography revealed C1-C-2 arthrodesis bone graft fusion after an average of 3.1 months (2–4 mo). There was no recurrence of symptoms and no dislocations or internal fixation device loosening or breakage. Conclusion: AARF with a locked C1–C2 lateral facet is a new type of AARF that cannot be classified using Fielding and Hawkins' classification. The anterior retropharyngeal approach for the release and reduction of AARF, followed by posterior C1–C2 arthrodesis is an effective therapeutic strategy for AARF with a locked C1–C2 lateral facet. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the text